2018
DOI: 10.1371/journal.pone.0199443
|View full text |Cite
|
Sign up to set email alerts
|

Auditory traits of "own voice"

Abstract: People perceive their recorded voice differently from their actively spoken voice. The uncanny valley theory proposes that as an object approaches humanlike characteristics, there is an increase in the sense of familiarity; however, eventually a point is reached where the object becomes strangely similar and makes us feel uneasy. The feeling of discomfort experienced when people hear their recorded voice may correspond to the floor of the proposed uncanny valley. To overcome the feeling of eeriness of own-voic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 28 publications
(29 reference statements)
4
24
0
Order By: Relevance
“…The filter type rated as the most similar to the own-voice differed across subjects. This individual difference was consistent with our previous study 14 . Such individual differences are reasonable because the bone structures and frequencies of the voices were different across subjects, and the magnitudes of bone and air conduction depend on the sound frequency 44 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The filter type rated as the most similar to the own-voice differed across subjects. This individual difference was consistent with our previous study 14 . Such individual differences are reasonable because the bone structures and frequencies of the voices were different across subjects, and the magnitudes of bone and air conduction depend on the sound frequency 44 .…”
Section: Discussionsupporting
confidence: 94%
“…In the fMRI scanner, 3 subjects chose the raw recorded voice as most representative of their own voice, while 14 rated the modified voices as most like their own voice. Individual differences were found in the own-voice scores in both environments, indicating that there was no general filter that could reproduce own-voice, as we previously reported 14 . Even though each subject tried to reproduce their own voice by adjusting the pitch, vibrato, and frequency cut-off filter, only a few subjects rated the adjusted voice as the one most similar to their own voice.…”
Section: Resultssupporting
confidence: 42%
See 1 more Smart Citation
“…The results of Experiment 2 showed that people rated their recorded voice and the “loudness+/−10 dB” audio recordings as more attractive than the “pitch+/−20 Hz” audio recordings. In recent years, an increasing number of studies have found that people like their recorded voices (Fraccaro et al, ; Hughes & Harrison, ), as people are tending to use more recording equipment or software in the modern digital media age and have thus become more familiar with their recorded voices (Kimura & Yotsumoto, ). This familiarity may result in liking.…”
Section: Discussionmentioning
confidence: 99%
“…Although recordings of self-voice can produce a feeling of eeriness for listeners as compared to when spoken (Kimura et al, 2018), people nevertheless recognize recorded voice samples as their own (Nakamura et al, 2001;Kaplan et al, 2008;Rosa et al, 2008;Hughes & Nicholson, 2010;Xu et al, 2013;Candini et al, 2014;Pinheiro et al, 2016aPinheiro et al, , 2016bPinheiro et al, , 2019. However, in ambiguous conditions (i.e.…”
Section: Variability In Self-monitoring Thresholdsmentioning
confidence: 99%